Investigation on Heterogeneous Influence of Government Subsidies on Pollution Reduction of Power Companies and Its Influencing Mechanism - Wang, Qin; Zheng, Xiaoqi; Yue, Zhonggang (Frontiers in Energy Research, 2022)
This study aims to investigate whether the subsidies promote pollution reduction or not by taking the power companies in China as a case study. So, we built a fixed-effects panel data model first, which is then used to verify the influence of government subsidies on pollution reduction in power companies. Additionally, how the subsidy influencing mechanism would work is also investigated. Results find that subsidies can significantly reduce power companies’ pollution, especially sulfur dioxide emissions and soot. At the same time, the result also showed that the government subsidies could encourage power companies to cut emissions by taking measures like end-of-pipe control and green innovation. Also, from the perspective of heterogeneity, government subsidies have a better effect on the regions with stronger environmental regulations, less economically developed regions, big-scale companies, and companies with low slack.